Steatosis and hepatic markers before and shortly after bariatric surgery - de Abreu, M. R. A.; Ramos, A. P. P.; Vendramini, Regina Célia [UNESP]; Burnetti, I. L.; Pepato, Maria Teresa [UNESP] (Royal Soc Medicine Press Ltd, 2007)
Background We present new findings on liver steatosis detected in a group of 20 morbidly obese patients who were reassessed shortly after bariatric surgery (BS) by assaying hepatic markers in their serum.Methods We assayed aspartate aminotransferase (AST), alanine aminotransferase, lactate dehydrogenase, alkaline phosphatase, gamma-glutamyl transferase (gamma-GT), cholinesterase, cholesterol, total protein, and albumin, and measured the weight and the body mass index (BMI) of patients, before and one and three months after surgery.Results There were significant reductions in BMI following surgery and also falls in transaminases and gamma-GT activities three months after BS. No changes occurred in other parameters between periods, except that cholesterol was above reference values before BS and fell to normal levels three months after BS.Conclusions We suggest that before undergoing surgery, the patients suffered from slight steatosis, while after BS the reduction in AST and gamma-GT indicated that this condition was corrected within three months. Moreover, these enzymes may be useful markers for excess fat in the liver.